Building governance capacity through institutional reforms: the Malaysian experience / Norhaslinda Jamaiudin - Jamaiudin, Norhaslinda (Universiti Teknologi MARA, 2021)
The concept of 'New Malaysia" was envisioned by Pakatan Harapan (PH) as part of their political pledges to build better governance capacity through institutional reforms. This was seen as a decisive move in view of a widening trust deficit between the government and society. Driven by this interest, this study aims to gauge the significant impact of institutional reforms in its professed ability to support the good governance agenda and to elevate public trust towards the government. Primary data was collected from 203 respondents via a survey questionnaire. The findings show that efforts to improve governance capacity via institutional reforms were commendable with more than 45 per cent respondents rating reforms as above par. Attempts to elevate a sense of trust in government is evident with 32.5 per cent of the total variability in public trust being accounted for by institutional reforms. This research adds to the body of knowledge relating to important corollary of institutional reforms towards better political governance in Malaysia.